Speciation and bioavailibility of rare earth elements (REEs) in ex-tin mining area: A case study from Lahat, Perak, Malaysia / Aysha Masood Khan - Aysha, Masood Khan (2017)
The main purpose of the study was to correlate the concentrations of rare earth elements (REEs), speciation and bioavailability. This study was proposed to investigate the distribution of REEs in abandoned mining land in Perak, Malaysia. Inductively coupled plasma mass spectrometry (ICP-MS) was used as major technique in this research. In this work, water, soil, sediment and plant samples were collected in the ex-tin mining area in Lahat, Perak, Malaysia in order to study the concentration, speciation, bioavailability and potential mobility of REEs. Water from ex-mining lakes and Kinta River was analyzed along with sediments. The results obtained revealed that the ex-mining lake water was found to be higher in REEs than that of the river water. The sediment samples were found highly accumulated with REEs. The analytical data obtained in this study was then analyzed using various chemometric methods such as principal component analysis (PCA), factor analysis (FA) and hierarchal cluster analysis (HCA). From the elemental analysis of ICP-MS, it is observed that soil samples taken from different depths in Perak were well separated into two clusters based on rare earth element concentrations and physical properties. The statistical analysis also indicated that REEs were the discriminating factors for the separation of soil samples at the depth of 0-20 cm from the rest. In addition, the samples taken from industrial and mining areas were clustered away from natural and residential areas, suggesting ex-mining and industries being the major source of REEs in the studied area. Different environmental impact assessments were done using enrichment factor (EF), geoaccumulation index (Igeo), contamination factor (CF) and pollution load index (PLI). Speciation study carried out for sediment and soil using sequential extraction procedures, indicate REEs mainly predominated in the adsorbed/exchangeable/carbonate fraction and in bound to silicates/residuals fraction while very small amounts of REEs were found bound to sulphides/organics and amorphous and crystalline Fe oxides. REEs were clearly separated into five fractions of sequential extractions indicating their active mobility in the environment. The data obtained successfully measures the potential mobility of REEs and significantly describe higher for light rare earth elements (LREEs) rather than heavy rare earth elements (HREEs). Bioavailability of REEs indicate most of the plants as hyperaccumulators in their root and leaves parts while others accumulator and tolerant. Transfer factor (TF), bioconcentration factor (BCF) and bioaccumulation factor (BAF) analyzed were > 1 for hyperaccumulators, making them good phytoremediators for REEs. Based on the analytical method, chemometric techniques and environmental impact factors, it can be concluded that even though physical and chemical variables vary from sample to sample, distinct separation between samples from different areas of ex-mining land can be clearly observed.